2005
DOI: 10.12968/ijpn.2005.11.2.17671
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a pilot nurse-led, community-based treatment programme for lymphoedema

Abstract: lymphoedema treatment programmes must ensure that the multidimensional impact of this symptom on women's lives is recognized and addressed as part of the treatment process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Four care programs were found in Australia [31], [32], [33], [34]. Three were found in Canada [35], [36], [37]. Two care programs were developed in the United States [38], [39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four care programs were found in Australia [31], [32], [33], [34]. Three were found in Canada [35], [36], [37]. Two care programs were developed in the United States [38], [39].…”
Section: Resultsmentioning
confidence: 99%
“…Patients in these reviewed care programs were with several common cancer diagnoses. Seven care programs served patients with single diagnosis, including breast cancer [24], [35], prostate cancer [19], [20], [34], colorectal cancer [21], [22], [32], and lung cancer [26]. Four care programs were designed for patients with cancers in the same specialty, including two programs for hematological malignancies [31], [36], two programs for head and neck cancer ( [25], [30], and one program for gynecological cancers [39].…”
Section: Resultsmentioning
confidence: 99%
“…Four (40%) studies were found in the LILACS database, five (50%) were found in PubMed, and one (10%) was found in CINAHL. Regarding the journals, one (10%) article was published in Revista Latino-Americana de Enfermagem, one (10%) was published in Escola Enfermagem Anna Nery, one (10%) was published in Revista Brasileira Ginecologia e Obstetrícia, one (10%) was published in Acta Paulista de Enfermagem, one (10%) was published in the Indian Journal of Cancer, one (10%) was published in The Breast, one (10%) was published in the Journal of Clinical Oncology, and one (10%) was Regarding the methodological design of the studies, one (10%) was a randomized controlled clinical trial [14]; one (10%) was a non-controlled randomized clinical trial [15]; two (20%) were cohort studies [16,17], and six (60%) were case-control studies [2,5,[18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…One study classified the grade of lymphedema as stages II and III [20], one (10%) study described it as grades I and II [15], and eight (80%) studies classified lymphedema as mild, moderate, or severe [2,5,14,16-19 21]. ,…”
Section: Resultsmentioning
confidence: 99%
“…It was unknown if her quality of life would have improved if her lymphoedema did not drastically reduce. Weiss and Spray (2002) found that the quality of life of patients with lymphoedema improves significantly after Complete Decongestive Therapy, irrespective of the limb volume decrease, but Howell and Watson (2005) found the exact opposite. These authors (Howell & Watson 2005) report that despite a limb volume reduction, the quality of life of most women in their study worsened as they realised that their lymphoedema would require lifelong management and would therefore serve as a reminder of their breast cancer experience.…”
Section: Discussionmentioning
confidence: 99%